CULTIVATING STUDENT CREATIVITY THROUGH CRAFTS FROM USED GOODS: IMPLEMENTATION OF CREATIVE DIMENSIONS IN P5 - Nur Ali Yasin; Mohammad Nurul Yaqin; Febby Eka Elsalina (JF Publisher, 2024)
The untidy school environment, especially the presence of scattered used goods such as cardboard, plastic bottles, and paper, is a problem that is often encountered at SDN 2 Kalipuro. This problem is not only related to cleanliness, but also shows the need for learning that builds students' awareness and creativity. This study aims to describe how the activity of utilizing used goods through making crafts can foster students' creativity as an implementation of the creative dimension in the Pancasila Student Profile Strengthening Project (P5). This study uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results of the study showed that the activity was carried out through several stages, namely collecting materials, planning designs, making works, and exhibiting the results. The exhibition of works was held to coincide with the distribution of report cards and was attended by parents, which was a form of appreciation for the students' work. This activity succeeded in fostering students' creativity in the form of original ideas, technical skills, and the ability to collaborate. In addition, this activity has a positive impact on character formation, such as responsibility, concern for the environment, and self-confidence. Thus, craft activities from used goods have proven to be effective as a contextual learning strategy that supports the strengthening of the creative dimension in P5.